Pengenalan Dan Pelatihan Pemrograman Bahasa Python Pada Smk Negeri 1 Sorong - Sandag, Green Arther; Mambu, Joe Yuan; Mandias, Green; Waworundeng, Jacquline (Servitium Smart Journal, 2024)
The world of education today cannot be separated from the influence of the development of information technology. Many students today get information related to technological developments from smartphones, websites, and video games. Learning at school also uses technology such as power point, zoom, and so on. Lately many schools and parents are encouraging children to learn programming. Programming is a way of giving commands to the computer to do something. There are several benefits in learning programming for students, such as sharpening the ability to communicate thoughts in a structured and logical manner, encouraging creativity, solving problems on their own, practicing communication skills, and teaching perseverance. Therefore, we introduce python programming at SMK Negeri 1 Sorong. The methods used during the programming training are the introduction of the python programming language, the practice of making simple programs, and the evaluation of students' abilities in programming the python programming language. During the training, it was found that the students had programmed before, but still had problems in writing the program. This training discusses programming syntax, variables, input, process, and output in python programming. The results of the evaluation in this activity students have understood the basic concepts of python programming with an average result of 80%.